PENGARUH RETURN ON EQUITY (ROE) DAN PRICE EARNING RATIO (PER) TERHADAP HARGA SAHAM PERUSAHAAN MANUFAKTUR SUB SEKTOR FARMASI DI BURSA EFEK INDONESIA - Mariyam Zanariah; Azmir Ferdinansyah (Fakultas Ekonomi Universitas Tridinanti Palembang, 2021)
The research aims to find out whether Return On Equity (ROE), Price Earning Ratio (PER) affects both partial and simultaneous to the stock price of the Manufacturing Company with Pharmaceutical sub sector in the Indonesia Stock Exchange. The research population is the Manufacturing Company with Pharmaceuticals Sub Sector listed in Indonesia Stock Exchange (BEI) in 2021 amounted 12 companies. The sampling technique was purposive sampling, so based on these criteria,the sample is 8 companies from 2015 to 2018.Following the analysis of multiple Linear Regression, also normality test, classic test, as well as hypotheses test both partially and simultaneously, the result is that the variable Return on Equity (ROE) and Price Earning Ratio (PER) significantly affect the Stock Price of Manufacturing Corporation of the Indonesian Stock Exchange. As a consideration for investors who will invest in stocks can observe the company's financial performance first, one of which is through analysis of financial statements. Thus it can maximize the benefits and minimize the risk in investing. Investor who will invest in stock should consider stock price because It is one of success indicator for company in managing its business.